AACSB workshop with Professor Dr. Che Ruhana Isa@Mohamed Isa - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
We had the honor of welcoming Professor Dr. Che Ruhana Isa@Mohamed Isa from Universiti Malaya (UM) as our guest for a session on AACSB accreditation. Held at Hotel UITM Shah Alam, the event was a remarkable success and provided invaluable insights into the accreditation process. Professor Dr. Che Ruhana delivered a comprehensive analysis of the AACSB accreditation process, sharing her extensive knowledge and experience. Attendees received practical guidance and strategies for effectively preparing for the Peer Review Team (PRT) visit, helping them navigate the accreditation process with greater confidence. The session featured an engaging Q&A segment, where participants had the opportunity to discuss specific challenges and solutions with Professor Dr. Che Ruhana.We extend our heartfelt gratitude to Professor Dr. Che Ruhana Isa@Mohamed Isa for her invaluable insights into the accreditation process and to all who attended the session. Your participation made the event a success and contributed to a deeper understanding of AACSB accreditation. Special thanks go to the AAGBS Quality Assurance and Accreditation team, led by Assoc. Prof. Dr. Hadijah Iberahim (Head of AAGBS Quality Assurance and Accreditation), along with AAGBS Top Management, Professors, Heads, Coordinators, Lecturers, and Administrative Staff, for their contributions and participation.